Analisis Konten Visual Tentang Isu Lingkungan Pada Akun Instagram @Walikota Palembang - Niya Sandiya; Aliasan .; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to identify the types of content on the Mayor of Palembang's Instagram account and how these posts address environmental issues. This study uses a qualitative methodology involving content analysis techniques. The data sources consist of photos and videos uploaded to the Mayor of Palembang's Instagram account related to environmental issues. Documentation and non- participatory observation were used as data collection methods. The analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that the content displayed covers government activities, development, social community, and environmental issues, where environmental visual content is presented through documentation of activities such as community service, waste management, and reforestation that highlight the mayor's direct involvement, thereby building an image of environmentally conscious leadership and encouraging community participation in maintaining the cleanliness and sustainability of the city.